RANCANGAN MEDIA MINIATUR PLTB BERBASIS 7TH SDGS UNTUK MEMFASILTASI CRITICAL THINKING PADA MATERI ENERGI - Fitry Fakhirah Azahra; Akhmad Nugraha; Agnestasia Ramadhani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning by using tools in the form of media is one way to improve the quality and interest of students' learning. The use of learning media in schools is very limited, so media development in learning is needed. Researchers aim to use the development of miniature PLTB (Wind Power Plant) media based on the 7th SDGs to facilitate critical thinking on energy material, the media used is valid and suitable for use. PLTB media development uses the ADDIE method with several stages as follows: analysis, planning, development, implementation, and evaluation. The products that have been developed are validated by media experts and material experts, data collection using a questionnaire by providing an assessment sheet by 1 media expert and 1 science material expert lecturer. The results of validation from media experts get a score of 77.33% which is included in the “Valid” criteria and for material experts get a score of 81.33% which is included in the “Very Valid” criteria. Thus, the miniature PLTB media that has been developed is suitable for use in learning science in elementary schools on energy material.